FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT SUKU BUNGA DEPOSITO BERJANGKA PADA BANK UMUM INDONESIA: STUDI LITERATUR - Rajagukguk, Eska H; Manurung, Valentina; Enjel Sitinjak, Dian Mika; Siallagan, E. Hamonangan; Hasugian, Christnova (Komunitas Manajemen Kompetitif, 2025)
This research aims to analyze the factors influencing the interest rate of time deposits in commercial banks through a literature review approach. The time deposit interest rate is one of the crucial instruments in the banking sector, reflecting the cost of funds for banks and influencing customer decisions in saving. In this study, we identify various factors contributing to interest rate determination, including macroeconomic conditions, monetary policy, interbank competition, and liquidity risk. Furthermore, this research also discusses the role of inflation and market expectations on time deposit interest rates. By analyzing existing literature, this research is expected to provide deeper insights into the dynamics of time deposit interest rates and their implications for bank asset and liability management. The findings of this research can serve as a reference for practitioners and academics in understanding the factors influencing deposit interest rates, and assist banks in formulating more effective interest rate setting strategies